Hesiod, the other poet : ancient reception of a cultural icon - Koning, Hugo H. (Mnemosyne, Supplements, 2010)
Hesiod: The Other Poet is a study dealing with the role of Hesiod in the imagination and the collective memory of the ancient Greeks. Its main hypothesis is that Hesiod's image was to a large degree formed by the picture of Homer: Hesiod is decidedly different when presented as allied with, opposed to or simply without Homer. Following this approach, Hesiod is investigated as a moral and philosophical authority, a locus informed with values and qualities, a concept in literary-critical discourse, and more generally as a cultural and panhellenic icon constructed and reconstructed by later Greek authors who employed and so re-created him in their own texts.